Determination of the delivered hemodialysis dose using standard methods and on-line clearance monitoring - Vlatković Vlastimir; Stojimirović Biljana (Vojnosanitetski Pregled)
Background/aim: Delivered dialysis dose has a cumulative effect and significant influence upon the adequacy of dialysis, quality of life and development of co-morbidity at patients on dialysis. Thus, a great attention is given to the optimization of dialysis treatment. On-line Clearance Monitoring (OCM) allows a precise and continuous measurement of the delivered dialysis dose. Kt/V index (K = dialyzer clearance of urea; t = dialysis time; V = patient's total body water), measured in real time is used as a unit for expressing the dialysis dose. The aim of this research was to perform a comparative assessment of the delivered dialysis dose by the application of the standard measurement methods and a module for continuous clearance monitoring. Methods. The study encompassed 105 patients who had been on the chronic hemodialysis program for more than three months, three times a week. By random choice, one treatment per each controlled patient was taken. All the treatments understood bicarbonate dialysis. The delivered dialysis dose was determined by the calculation of mathematical models: Urea Reduction Ratio (URR) singlepool index Kt/V (spKt/V) and by the application of OCM. Results. Urea Reduction Ratio was the most sensitive parameter for the assessment and, at the same time, it was in the strongest correlation with the other two, spKt/V indexes and OCM. The values pointed out an adequate dialysis dose. The URR values were significantly higher in women than in men, p < 0.05. The other applied model for the delivered dialysis dose measurement was Kt/V index. The obtained values showed that the dialysis dose was adequate, and that, according to this parameter, the women had significantly better dialysis, then the men p < 0.05. According to the OCM, the average value was slightly lower than the adequate one. The women had a satisfactory dialysis according to this index as well, while the delivered dialysis dose was insufficient in men. The difference between the women and the men was significant. Conclusion. The application of OCM has shown that it is the most rigorous parameter for the assessment of adequacy and that its regular use would contribute to increasing of the delivered dialysis dose and improvement of the treatment quality.